Minocycline and Doxycycline, but not Tetracycline, Mitigate Liver and Kidney Injury after Hemorrhagic Shock/Resuscitation - Kholmukhamedov, Andaleb (2014)
BACKGROUND: Despite recovery of hemodynamics by fluid resuscitation after hemorrhage, development of the systemic inflammatory response and multiple organ dysfunction syndromes can nonetheless lead to death. Minocycline and doxycycline are tetracycline derivatives that are protective in models of hypoxic, ischemic and oxidative stress. Our Aim was to determine whether minocycline and doxycycline protect liver and kidney and improve survival in a mouse model of hemorrhagic shock and resuscitation. METHODS: Mice were hemorrhaged to 30 mm Hg for 3 h and then resuscitated with shed blood followed by half the shed volume of lactated Ringer's solution containing tetracycline (10 mg/kg), minocycline (10 mg/kg), doxycycline (5 mg/kg) or vehicle. For pre-plus post-treatment, drugs were administered intraperitoneally prior to hemorrhage followed by second equal dose in Ringer's solution after blood resuscitation. Blood and tissue were harvested after 6 h. RESULTS: Serum alanine aminotransferase (ALT) increased to 1988 and 1878 U/L after post-treatment with vehicle and tetracycline, respectively, whereas minocycline and doxycycline post-treatment decreased ALT to 857 and 863 U/L. Pre-plus post-treatment with minocycline and doxycycline also decreased ALT to 849 and 834 U/L. After vehicle, blood creatinine increased to 279 μM, which minocycline and doxycycline post-treatment decreased to 118 and 112 μM. Minocycline and doxycycline pre- plus post-treatment decreased creatinine similarly. Minocycline and doxycycline also decreased necrosis and apoptosis in liver and apoptosis in both liver and kidney, the latter assessed by TUNEL and caspase-3 activation. Lastly after 4.5 h of hemorrhage followed by resuscitation, minocycline and doxycycline (but not tetracycline) post-treatment improved 1-week survival from 38%(vehicle) to 69% and 67%, respectively. CONCLUSION: Minocycline and doxycycline were similarly protective when given before as after blood resuscitation and might therefore have clinical efficacy to mitigate liver and kidney injury after resuscitated hemorrhage.